PENGARUH FAKTOR PSIKOLOGIS TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN MICE MELALUI PT. Y&R KE BALI - Masni Nistari, Ni Putu; Sudana, I Putu; Sasrawan Mananda, I GPB. (Jurnal IPTA (Industri Perjalanan Wisata), 2016)
Tourism is a global industry sectors and potentially to be developed as a source of government income countries and regions. MICE (Meeting, Incentive, Convention and Exhibition) in Indonesia has great potential and is the flagship product of the tourism industry Indonesia. The purpose of this research is to determine the influence of psychological factors toward MICE tourists visiting decision to Bali through PT. Y&R. Sampling technique used in this research is purposive sampling. Samples are 100 respondents and sampling method is accidental sampling. Test instrument used are validity, reliability and test the classical assumption of normality test, multicollinearity, and heteroscedasticity test. Data were analyzed using multiple linear regression analysis. The results of hypothesis testing psychological factor partially and simultaneously the t test and F test is a significant effect and positive value to the decision of MICE tourists visited through PT. Y & R to Bali. Based on the analysis of multiple test showed that psychological factors have a positive coefficient values consisting of motivation (X1) of 0.216, perception (X2) is 0.298, learning (X3) of 0.370, beliefs and attitudes (X4) of 0.212 against the decision to visit. Value Adjusted R Square of 0.610 or 61.0% of decision variables been influenced by psychological factors, while 39.0% describe by other causes beyond the variables studied.
Keywords: The Influence, Decision to Visit, Psychological Factors, MICE